2013
DOI: 10.4103/0972-124x.113076
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A: Novel biomarker between periodontal disease and psychosocial stress

Abstract: Context:The psychosocial stress has long been regarded as a significant pre-disposing factor for periodontal disease. The association between the periodontal disease and the neuroendocrine hormones has been observed. Chromogranin A (CgA) is supposed to link the activity of the neuroendocrine system to local and systemic immune functions and to be related to periodontitis.Aims:The aim of this study was to determine the CgA levels in saliva and plasma in periodontal health and disease and to assess their potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Chromogranin A and its derived peptides have shown promise as biomarkers for cardiovascular diseases such as hypertension, heart failure, myocardial infarction, and coronary syndromes [4347]. Moreover, saliva CgA has been shown to be a sensitive biomarker for stress in humans and pigs [12, 14, 4853]. Some evidence suggests that CgA could be useful as a biomarker for neuroendocrine tumors and stress also in dogs [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…Chromogranin A and its derived peptides have shown promise as biomarkers for cardiovascular diseases such as hypertension, heart failure, myocardial infarction, and coronary syndromes [4347]. Moreover, saliva CgA has been shown to be a sensitive biomarker for stress in humans and pigs [12, 14, 4853]. Some evidence suggests that CgA could be useful as a biomarker for neuroendocrine tumors and stress also in dogs [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…This study suggested that chronic psychological stress may influence sCgA secretion via chronic stress-related attenuation of the activity of the sympathetic-adrenomedullary system in healthy adult males. Reshma et al 18 reported that the levels of CgA in the plasma and saliva were elevated in subjects with stress-induced chronic periodontitis. There were inconsistent results of sCgA secretion in response to chronic stress.…”
Section: Resultsmentioning
confidence: 99%
“…A possible influence of all these factors on our results cannot be completely excluded, since patterns of behavior and genetic polymorphisms were not assessed. Furthermore, sCgA concentrations were described to be affected by several pathologies, such as aggressive [48] or chronic periodontitis [51], bruxism [52], type 2 diabetes [53], or xerostomia (dry mouth) [54]; in general the presence of these pathologies was associated with higher sCgA level. In addition, as our study participants were older subjects, they are administrated a wide variety of medications which may also affect the sCgA secretion.…”
Section: Discussionmentioning
confidence: 99%